Identifying playing talent in professional football using artificial neural networks. Issue 11 (17th June 2020) - Barron, Donald; Ball, Graham; Robins, Matthew; Sunderland, Caroline
ABSTRACT: The aim of the current study was to objectively identify position-specific key performance indicators in professional football that predict out-field players league status. The sample consisted of 966 out-field players who completed the full 90 minutes in a match during the 2008/09 or 2009/10 season in the Football League Championship. Players were assigned to one of three categories (0, 1 and 2) based on where they completed most of their match time in the following season, and then split based on five playing positions. 340 performance, biographical and esteem variables were analysed using a Stepwise Artificial Neural Network approach. The models correctly predicted between 72.7% and 100% of test cases (Mean prediction of models = 85.9%), the test error ranged from 1.0% to 9.8% (Mean test error of models = 6.3%). Variables related to passing, shooting, regaining possession and international appearances were key factors in the predictive models. This is highly significant as objective position-specific predictors of players league status have not previously been published. The method could be used to aid the identification and comparison of transfer targets as part of the due diligence process in professional football.